(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
To contextualize the disagreement between the traditional mentalistic assumption and radical behaviorism about the concepts of causation and explanation, this paper presents a review and a critical analysis of Peter Strawson’s action theory, based in supposed links between the concepts of belief, attitude, and desire. Such concepts can be seen as complex behavioral processes and as natural phenomena which involve functional relations between rules, operant behavior and establishing operations. We try to eliminate the Strawson’s distinction between causation and explanation. Our gist is that for radical behaviorism the important fact is that contingencies which promote the knowledge involve nothing more than stimuli and responses, without mediating processes.